Human Neutrophil Defensin-1, -3, and -4 Are Elevated in Nasal Aspirates from Children with Naturally Occurring Adenovirus Infection - V. S. Priyadharshini; F. Ramírez-Jiménez; M. Molina-Macip; C. Renteria-Rosales; J. Santiago-Cruz; Paola Zarate-Segura; E. Lara-Padilla; Luis M. Teran (Canadian Respiratory Journal)
Background. Adenoviruses are highly contagious pathogens which cause respiratory disease particularly in children; they may induce severe disease in infants. Human neutrophil peptides (HNPs) have been found to exhibit antiadenoviral activity. Thus, we have investigated HNPs in nasal aspirates (NAs) of children suffering from adenoviral common cold. Objective. To investigate the release of HNP-1–4 in adenovirus infection and the relationship with self-limiting upper respiratory tract infections. Methods. Nasal aspirate samples (n=14) were obtained from children (aged 6–12 years) infected with adenovirus between June 2012 and December 2015. Control samples were taken 4 weeks after infection when the children were asymptomatic. Levels of HNPs were measured using an enzyme-linked immunosorbent assay (ELISA). Results. There were increased levels of HNP-1, -3, and -4, but not HNP-2, in nasal aspirates (NAs) during adenovirus infections compared to healthy specimens (p≤0.01). Moreover, there was also increase in the neutrophil count, which is a known cell source of HNPs. Conclusion. Our finding supports the involvement of HNP-1, -3, and -4 in naturally occurring cold in children infected with adenovirus. Because of their known antiviral properties, it is tempting to hypothesize that HNPs might play a protective role in adenovirus-induced respiratory disease; however, this remains to be shown.